Protective and Pathogenic Roles of CD8+ T Lymphocytes in Murine Orientia tsutsugamushi Infection. - Matthias Hauptmann; Julia Kolbaum; Stefanie Lilla; David Wozniak; Mohammad Gharaibeh; Bernhard Fleischer; Christian A Keller (Public Library of Science (PLoS), 2016)
T cells are known to contribute to immune protection against scrub typhus, a potentially fatal infection caused by the obligate intracellular bacterium Orientia (O.) tsutsugamushi. However, the contribution of CD8+ T cells to protection and pathogenesis during O. tsutsugamushi infection is still unknown. Using our recently developed BALB/c mouse model that is based on footpad inoculation of the human-pathogenic Karp strain, we show that activated CD8+ T cells infiltrate spleen and lung during the third week of infection. Depletion of CD8+ T cells with monoclonal antibodies resulted in uncontrolled pathogen growth and mortality. Adoptive transfer of CD8+ T cells from infected animals protected naïve BALB/c mice from lethal outcome of intraperitoneal challenge. In C57Bl/6 mice, the pulmonary lymphocyte compartment showed an increased percentage of CD8+ T cells for at least 135 days post O. tsutsugamushi infection. Depletion of CD8+ T cells at 84 days post infection caused reactivation of bacterial growth. In CD8+ T cell-deficient beta 2-microglobulin knockout mice, bacterial replication was uncontrolled, and all mice succumbed to the infection, despite higher serum IFN-γ levels and stronger macrophage responses in liver and lung. Moreover, we show that CD8+ T cells but not NKT cells were required for hepatocyte injury: elevated concentrations of serum alanine aminotransferase and infection-induced subcapsular necrotic liver lesions surrounded by macrophages were found in C57Bl/6 and CD1d-deficient mice, but not in beta 2-microglobulin knockout mice. In the lungs, peribronchial macrophage infiltrations also depended on CD8+ T cells. In summary, our results demonstrate that CD8+ T cells restrict growth of O. tsutsugamushi during acute and persistent infection, and are required to protect from lethal infections in BALB/c and C57BL/6 mice. However, they also elicit specific pathologic tissue lesions in liver and lung.